Alte Melodieformeln in neuen Kirchenliedern - Smilde, Bernard (Jahrbuch für Liturgik und Hymnologie, 1982)
Composing a new diatonic and singable hymn tune for the congregation today will often mean unintentionally adopting note-patterns established in earlier centuries. Such phrases from the sixteenth century are especially appropriate for this use. This is shown in an example from the Liedboek voor de Kerken, the hymn book that five Dutch churches have been using since 1975. The tune (No. 487), composed by B. Huibers, has hardly a note that does not have an earlier model. Sequences of notes from the classic period of the Reformation, especially from the Genevan Psalter (1562), continue to appear in a composer's thoughts. What is particularly interesting in this case is that the composer is a Roman Catholic whose familiarity with the Genevan Psalter cannot be taken for granted. This underlines the artistic and pedagogical achievement of L. Bourgeous and the other composers of the melodies of the Hugenot psalter.